Sebaceous breast carcinoma: report of a rare histological special subtype - Wachter, David; Rauh, C.; Wenkel, Evelyn; Fasching, Peter; Beckmann, Matthias; Hartmann, Arndt (Pathologe, 2014)
We report on a case of sebaceous carcinoma of the breast as a rare histological special subtype of breast cancer. Because these tumors are uncommon, differential diagnostic considerations and the exclusion of Muir-Torre syndrome are emphasized. Finally possible mechanisms of development and therapeutic strategies for this carcinoma are discussed.
EVALuna2:6578